ظاهرة الدروس الخصوصية الاسباب والنتائج - دراسة ميدانية في مدينة الديوانية - - الدعمي شذى نجاح بلاش (lark, 2019)
Abstract This is the phenomenon of the important issues that extends impact positively and negatively on the students, school, family, and community, it adds a financial burden on the parents, if these funds, which consumes the private lessons in the public education system has invested possible to reduce the size of the educational waste, and realized benefit for all, as the spread in schools among students has led to many problems in high school and confronted with the sad reality of schools, the need calls for action to reduce the effects of this negative phenomenon in a scientific thoughtful, and to learn about the educational effects through the survey the views of students, teachers, and parents things, in this educational causes, effects and its relationship with some educational variables, as well as to know whether this phenomenon is positive or negative and that this study seeks to achieve its objectives by answering the question: It is tutoring positive or negative and fork from this question: What comes What causes the proliferation of private lessons from the perspective of parents, students and teachers What the consequences of the spread of private lessons.